2015
DOI: 10.1007/s00464-015-4241-7
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic gastrectomy for gastric cancer: comparison of short-term surgical outcomes

Abstract: The comparative study demonstrates that RAG is as acceptable as LAG in terms of surgical and oncologic outcomes. With lower estimated blood loss, acceptable complications, and radical resection, RAG is a promising approach for the treatment of gastric cancer. However, the indication of patients for RAG is critical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 29 publications
6
56
1
1
Order By: Relevance
“…For example, Vinuela et al [24] performed a meta-analysis of all English-language studies since 1992, including several from Eastern centers, and found that when they compared open versus laparoscopic distal gastrectomy outcomes, the former were associated with better lymph node harvest quantitatively, but no difference was seen in the odds of having less than the recommended minimum of lymph nodes on the basis of the approach alone. With regard to R0 resection rates, Shen et al's [21] findings concurred with those of the present study. Perhaps the more clinically significant observation is that newer, minimally invasive technology is noninferior to the standard open procedure and potentially offers faster healing, fewer wound complications, and an earlier use of adjuvant therapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For example, Vinuela et al [24] performed a meta-analysis of all English-language studies since 1992, including several from Eastern centers, and found that when they compared open versus laparoscopic distal gastrectomy outcomes, the former were associated with better lymph node harvest quantitatively, but no difference was seen in the odds of having less than the recommended minimum of lymph nodes on the basis of the approach alone. With regard to R0 resection rates, Shen et al's [21] findings concurred with those of the present study. Perhaps the more clinically significant observation is that newer, minimally invasive technology is noninferior to the standard open procedure and potentially offers faster healing, fewer wound complications, and an earlier use of adjuvant therapy.…”
Section: Discussionsupporting
confidence: 91%
“…Proponents of robotic technology, in particular, cite greater technical precision, more degrees of freedom in instrument articulation, and better visualization of anatomy relative to other surgical approaches [10]. With most of the experience and literature regarding surgery for gastric cancer coming from the East, previously published studies show a greater quantity of lymph nodes harvested during minimally invasive surgery, yet there is a general lack of consensus regarding improved R0 resection rates on the basis of the approach alone [11,[19][20][21][22][23]. For example, Vinuela et al [24] performed a meta-analysis of all English-language studies since 1992, including several from Eastern centers, and found that when they compared open versus laparoscopic distal gastrectomy outcomes, the former were associated with better lymph node harvest quantitatively, but no difference was seen in the odds of having less than the recommended minimum of lymph nodes on the basis of the approach alone.…”
Section: Discussionmentioning
confidence: 99%
“…Oncological outcomes other than survival or recurrence, such as the number of lymph nodes harvested and margin status, are reported to be similar between robotic and laparoscopic approaches30 (Table 1). However, a potential advantage of robotic surgery was found in carrying out D2 lymphadenectomy.…”
Section: Oncological Outcomesmentioning
confidence: 96%
“…On the contrary, robotic surgery shows comparable or better retrieval of lymph nodes than laparoscopy (16,17,19,21,23,25). The reduced number of retrieved lymph nodes is the one single weakness of laparoscopic surgery, compared with open surgery, for which robotic systems can compensate.…”
Section: Higher Number Of Retrieved Lymph Nodesmentioning
confidence: 99%
“…In robotic gastrectomy, about half of all publications report less bleeding than that in laparoscopic surgery (7,17,20,(23)(24)(25)(26)(27)(28). Statistically, less bleeding may have no impact on the clinical course of the patients; however, it implies that robots offer more precise dissection of the lymph nodes following the surgical plane.…”
Section: Less Bleedingmentioning
confidence: 99%